Application of Project Based Learning (PBL) Model for Materials of Salt Hydrolysis to Encourage Students' Entrepreneurship Behaviour - Carnawi, Carnawi; Sudarmin, Sudarmin; Wijayati, Nanik (International Journal of Active Learning, 2017)
This research aims to understand the influence of the application of PjBL model etnosains charged to the students entrepreneurial attitudes and learning outcomes to the matterial Hydrolysis Salt using experimental research and quantitative method Sampling was done using simple random sampling technique with research design using pretest-posttest control group design. Entrepreneur attitude and learning outcome obtained using the research instrument which is consist of observation sheet, questionnaire, and question sheet. Analysis of the growth of entrepreneurial attitude using score analysis with triple observation. Gender influence to entrepreneurial attitude analized using uji beda t-test and the analysis of learning outcome using n-gain and score analysis. The research results show that (1) attitude entrepreneurial students experienced growth all these aspects on experimental group and aspects confident on control group; (2) no gender affect attitude entrepreneurial students; (3) the value n-gain on theexperimental group is 0,51 and for control group is 0.13 the criteria are. While learning outcomes psychomotor 3,45 criteria it is good to experimental group and 3,10 criteria good for control group.